Case Report: Whole-exome sequencing revealed a de novo variant in SETBP1 gene in a Chinese family with developmental delay - Pan, Junlin; Zhang, Yan; Hou, Jinwei; Shi, Na; Qu, Huiling; Jiang, Longhuan; Liu, Haiping (Frontiers in Genetics, 2025)
BackgroundThis study aims to characterize the potential genetic etiologies in children with developmental delay through whole-exome sequencing (WES) providing assistance for clinical diagnosis, genetic counseling, and reproductive guidance.MethodsWES was performed on the proband, followed by Sanger sequencing validation of the identified variant in the parents.ResultsThe proband exhibits global developmental delay, including impaired motor and language development, reduced spontaneous speech, poor coordination, and attention deficits. WES revealed a heterozygous nonsense variant in SETBP1 (c.1630C>T, p.Arg544Ter), which was confirmed as de novo by Sanger sequencing. This variant was classified as pathogenic according to American College of Medical Genetics and Genomics (ACMG) guidelines. The patient was subsequently diagnosed with intellectual disability, autosomal dominant 29 (MRD29).ConclusionThe de novo SETBP1 p.Arg544Ter variant was identified as the underlying genetic cause in this case. Our findings underscore the importance of early genetic testing in children with developmental delay to enable precise diagnosis, informed genetic counseling, and evidence-based reproductive planning.